Controversies in the management of sudden sensorineural hearing loss: an evidence‐based review. (June 2015) - Lawrence, R.; Thevasagayam, R.
<x xml:space="preserve">Abstract</x> Background Sudden sensorineural hearing loss (SSNHL) is considered an otological emergency. It may present as an isolated condition or be the presenting feature of a systemic disease process. Idiopathic sudden sensorineural hearing loss (ISSNHL) is diagnosed when an underlying cause or condition cannot be identified. Objective of review To review the current literature on SSNHL and propose a treatment algorithm based on the highest quality evidence. Search strategy and type of review An evidence‐based literature review using medline (search terms 'sudden sensorineural hearing loss' and 'acute sensorineural hearing loss'). Results (i) Baseline Investigations: All patients should be assessed with a thorough history and examination. This should include a pure tone audiogram (PTA) where possible. Baseline and targeted laboratory tests should be carried out to diagnose specific conditions. (ii) Imaging: MRI should be carried out in all cases of ISSNHL. If MRI imaging is contraindicated either CT or auditory brainstem response (ABR) testing should be performed. (iii) Medical Management: If a specific cause for a SSNHL is found, the patient should be managed accordingly. If idiopathic in nature, patients may be offered a course of oral steroid. If systemic steroids are contraindicated and/or there is no improvement with initial oral therapy, intratympanic steroids (IT) as either primary or salvage therapy may be considered. (iv) Further Management: There is no evidence to support the routine use of antiviral therapy. The cost, limited availability and lack of strong evidence for hyperbaric oxygen therapy (HBOT) make it impractical at present. Due to the variability in the vasodilator and vasoactive agents used, there is insufficient evidence to support the routine use of these agents. Consideration should be given to both temporary and permanent hearing amplification when required. Conclusions SSNHL is an important condition that can have a significant impact on quality of life. Some patients respond spontaneously without intervention; however, evidence tells us that certain interventions such as corticosteroid treatment may improve outcomes. Further high‐quality research is required. Meanwhile, an interim indicative treatment algorithm for SSNHL based on the current best evidence available is outlined.